Você está na página 1de 54

 K

L L

n

n p n × p n × p

n n × n d(i, j) i j

f

sf

sf =

1

n (| x 1f m f | + | x 2f m f | + ··· + | x nf m f |),

x 1f , ··· , x nf

n f m f

f

m f =

1

n (x 1f + x 2f + ··· + x nf ).

z

z if = x if m f

s

f

.

z

d(i, j) = (| x i1 x j1 | 2 + | x i2 x j2 | 2 + ··· + | x ip x jp | 2 ),

i = (x i1 , x i2 ,

,

x ip ) j = (x j1 , x j2 ,

,

x jp ) p

d(i, j) =| x i1 x j1 | + | x i2 x j2 | + ··· + | x ip x jp |

.

d(i, j) = (| x i1 x j1 | q + | x i2 x j2 | q + ··· + | x ip x jp | q ) 1/q ,

q q = 1 q = 2

d(i, j) = w 1 | x i1 x j1 | q +w 2 | x i2 x j2 | q + ··· + | x ip x jp | 2 .

a 1 i j b 1 i 0 j c 0 i 1 j d 0 i j p (p = a + b + c + d)

 1 a b a + b 0 c d c + d a + c b + d p

b + c a + b +

d(i, j) =

c + d .

d

d(i, j) =

b + c

a + b + c .

i j

d(i, j) = p m ,

p

m i j

p

1

0

M

f n

f

f i x if f M f

, M f x if

1,

r if 1,

, M f

[0 1]

r if i f

z if = r if 1

M f

1 .

z if f i

f x if i y if = log(x if ) y if

x if

[0; 1]

p

f =1 , δ ij d ij

f

f

d(i, j) =

p

f =1 δ ij

f

,

f